Evaluating the impact of Warrior Watch: Behaviour change to promote human-lion coexistence. (July 2022) - Chausson, Alexandre; Gurd, Heather; Foley, James; Bhalla, Shivani; Lekilelei, Jeneria; Otieno, Tobias; Lejale, Ben; Lenasalia, Peter; Milner-Gulland, E.J.
Abstract: Promoting human-wildlife coexistence is one of the most complex and pressing global conservation challenges faced today, particularly for large carnivore species. Effective conservation of large carnivores rests on interventions fostering coexistence in human-dominated landscapes, across the large ranges on which they depend. However, there is a paucity of research evaluating such interventions, and impact on the social determinants of behavioural outcomes. To bridge this evidence gap, we evaluate the impact of Warrior Watch, a grassroots intervention established in 2010 that draws on the traditional social structures and roles of Samburu pastoralists in northern Kenya to mitigate human-lion conflict peacefully. Using a novel approach blending elements of theory-based methods and traditional impact evaluations, and tailored to local resources and capacities, we evaluate the impact of Warrior Watch on a) attitudes towards lions and b) killing intentions as a proxy for tolerance. We show that warriors in the intervention site reported significantly more positive attitudes towards lions and were significantly less likely to indicate intentions to kill lions than their counterparts in the comparison conservancy. Furthermore, respondents in the intervention site were significantly more likely to report positive changes in their attitudes and tolerance towards lions since the inception of Warrior Watch, and to attribute these changes to the intervention. Our study demonstrates how evaluations tailored to local capacities and resource-limited situations can produce robust insights to support the adaptive management of interventions and increase the evidence-base to guide conservation practice.